The Role of the Pancasila Student Profile Strengthening Project in Building Unity and Social Character in SMPN 9 Surabaya Students - Adi Suryanto; Pandu Rudy Widyatama (Penerbit Mandalika Indonesia, 2025)
This study aims to analyze the role of the Pancasila Student Profile Strengthening Project (P5) in building unity and social character in SMPN 9 Surabaya students. This project is designed to introduce and internalize the values of Pancasila, which include cooperation, cooperation, and appreciation for diversity, among students. This study uses a descriptive qualitative approach, with data collection through observation, interviews, and documentation. The results of the study show that the Pancasila Student Profile Strengthening Project (P5) has succeeded in strengthening students' social character, improving their ability to work together in groups, and strengthening social bonds between students. Activities such as making processed food, beverages, and eco-print batik provide opportunities for students to develop practical skills while increasing a sense of unity and sociality. Data obtained from observations and interviews revealed that students felt closer to their peers and were more able to cooperate after participating in this activity. However, challenges such as time and resource limitations are still obstacles in the implementation of this project. Therefore, it is recommended to improve training for teachers, involve parents and the community, and conduct periodic evaluations of the implementation of the program to ensure its effectiveness. Further research is needed to explore solutions to existing challenges.